The mediating effect of attitude on factors influencing participation in Domestic Solid Waste Management (DSWM) - Kilagwa, Rehema; Wok, Saodah; Ahmad, Zeti Azreen (2021)
Domestic solid waste management (DSWM) is a serious challenge in developing countries including Tanzania as most of its people are residing in an unplanned settlement where management of solid waste is very difficult. The efficiency of DSWM requires an effective participation from the local people, who are fully aware of and have a positive attitude as well as good perception regarding DSWM issues. Meanwhile, radio has a wide coverage in Tanzania. It should be an important medium for raising public awareness about DSWM as to easily influence their participation in DSWM issues. The objectives of this paper are to analyze the relationship between awareness, perception, attitude, and participation in DSWM in Dar es Salaam city, and to test the mediating effect of attitude on the relationship between awareness and perception on participation in DSWM. The study was guided by development communication theory (DevCom-theory). A total of 392 respondents participated in this study, which employed a quantitative research design using the survey method with questionnaire as its research instrument for data collection. The findings revealed a positive relationship among all variables. Attitude fully mediates the relationship between awareness and participation in DSWM, and partially between perception and participation.